Multilayered micro/nanocrystalline CVD diamond coatings for biotribology - Salgueiredo, Ermelinda da Conceição Portela (2015)
In the present work multilayered micro/nanocrystalline (MCD/NCD) diamond coatings were developed by Hot Filament Chemical Vapour Deposition (HFCVD). The aim was to minimize the surface roughness with a top NCD layer, to maximize adhesion onto the Si3N4 ceramic substrates with a starting MCD coating and to improve the mechanical resistance by the presence of MCD/NCD interfaces in these composite coatings. This set of features assures high wear resistance and low friction coefficients which, combined to diamond biocompatibility, set this material as ideal for biotribological applications. The deposition parameters of MCD were optimized using the Taguchi method, and two varieties of NCD were used: NCD-1, grown in a methane rich gas phase, and NCD-2 where a third gas, Argon, was added to the gas mixture. The best combination of surface pre-treatments in the Si3N4 substrates is obtained by polishing the substrates with a 15 μm diamond slurry, further dry etching with CF4 plasma for 10 minutes and final ultrasonic seeding in a diamond powder suspension in ethanol for 1 hour. The interfaces of the multilayered CVD diamond films were characterized with high detail using HRTEM, STEM-EDX and EELS. The results show that at the transition from MCD to NCD a thin precursor graphitic film is formed. On the contrary, the transition of the NCD to MCD grade is free of carbon structures other than diamond, as a result of the richer atomic hydrogen content and of the higher substrate temperature for MCD deposition. At those transitions, WC nanoparticles were found due to contamination from the filament, being also present at the first interface of the MCD layer with the silicon nitride substrate. In order to study the adhesion and mechanical resistance of the diamond coatings, indentation and particle jet blasting tests were conducted, as well as tribological experiments with homologous pairs. Indentation tests proved the superior behaviour of the multilayered coatings that attained a load of 800 N without delamination, when compared to the mono and bilayered ones. The multilayered diamond coatings also reveal the best solid particle erosion resistance, due to the MCD/NCD interfaces that act as crack deflectors. These results were confirmed by an analytical model on the stress field distribution based on the von Mises criterion. Regarding the tribological testing under dry sliding, multilayered coatings also exhibit the highest critical load values (200N for Multilayers with NCD-2). Low friction coefficient values in the range μ=0.02- 0.09 and wear coefficient values in the order of ~10-7 mm3 N-1 m-1 were obtained for the ball and flat specimens indicating a mild wear regime. Under lubrication with physiological fluids (HBSS e FBS), lower wear coefficient values ~10-9-10-8 mm3 N-1 m-1) were achieved, governed by the initial surface roughness and the effective contact pressure.